Smart energy systems applied at urban level: the case of the municipality of Bressanone-Brixen - Prina, Matteo Giacomo; Cozzini, Marco; Garegnani, Giulia; Moser, David; Filippi Oberegger, Ulrich; Vaccaro, Roberto; Sparber, Wolfram (International Journal of Sustainable Energy Planning and Management, 2016)
The present paper focuses on the energy system of the municipality of Bressanone-Brixen, located in the North of Italy. The aim of this paper is to investigate various possible energy scenarios for this case study in order to improve the overall efficiency of the system. The different scenarios include high penetration of photovoltaics at urban level, considering the maximum rooftop PV potential of the local area. Different solutions have been analyzed in order to study the handling of the consequent excess of electricity production. Electric storage and a solution combining heat pumps and thermal storage have been evaluated to maximize the local use of the generated electricity. A deterministic approach (without the use of an optimization algorithm) and a heuristic optimization approach have been applied to evaluate the different possible configurations. The present analysis can be of interest for other cities in a mountain environment where the production from renewables is limited by orographic constraints, energy consumption per capita is higher and stronger resiliency to climate change is needed.